Nghiên cứu hệ epoxy DER-331 đóng rắn bằng metyltetrahydrophtalic anhydrit (MTHPA) để chế tạo vật liệu compozit tiên tiến. Phần II. Ảnh hưởng của nanoclay đến sự đóng rắn của hệ epoxy DER-331/MTHPA/DMP-30. - Anh, Lê Hoài; Chương, Bùi; Thọ, Trần Như; Khiêm, Vũ Đình; Liên, Đinh Thị (Vietnam Journal of Chemistry, 2012)
Nanoclays were added to DER-331 epoxy cured with metyltetra hydro phatalic anhydride (MTHPA) and DMP-30 catalyst. Effect of adding nanoclay to the epoxy on cure reaction of the composites was studied by measuring gel contents.  X-ray diffraction (XRD) technique was employed to investigate the inter-planar distance between the nanoclay platelets in different samples. Scanning electron microscopy (SEM) was used to investigate the morphology of composites. The mechanical properties of the composites were characterized in terms of tensile, flexural and compression tests. The results show that adding nanoclay to the epoxy composites  decreases the gel contents of epoxy but increases the mechanical properties of the epoxy composites by 16% in tensile, 10% in compression and 16% in flexural strength.